Lifetime-Based pH Sensors: Indicators for Acidic Environments - Lin, Hai-Jui (Anal Biochem, 1999)
We characterized the pH-dependent intensity decays of three fluorophores, Oregon green 514 carboxylic acid, Cl-NERF, and DM-NERF, using frequency-domain fluorometry, with the objective of identifying lifetime-based sensors for low pH values. These three probes were originally designed as dual excitation wavelength–ratiometric probes, with high photostability and high quantum yields in aqueous solutions. We found that their fluorescence intensity decays were strongly dependent on pH. Moreover, global intensity decays analysis reveals that these probes have double exponential intensity decays at intermediate pH values and that the decay time amplitudes are greatly dependent on pH. The longer lifetime components originated from the unprotonated forms and the shorter components from the protonated forms. Both forms can emit fluorescence at intermediate pH values. The apparent pK(a) values were also determined from the titration curves of phase angles and modulations versus pH for the purpose of pH sensing. The apparent pK(a) values range from pH 3 to 5, a range where lifetime-based sensors are not presently reported. Since these probes show low pK(a) values and display substantial phase and modulation changes with pH, they are suitable as lifetime-based pH sensors to monitor the pH changes in acidic environments. One potential application of these probes is to trace the pH in different cellular compartments.